2015
DOI: 10.1021/acs.jmedchem.5b00184
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a β-Hairpin Octapeptide, c[Pro-Arg-Phe-Phe-Dap-Ala-Phe-DPro], Mimetic of Agouti-Related Protein(87–132) [AGRP(87–132)] with Equipotent Mouse Melanocortin-4 Receptor (mMC4R) Antagonist Pharmacology

Abstract: Agouti-related protein (AGRP) is a potent orexigenic peptide that antagonizes the melanocortin-3 and -4 receptors (MC3R and MC4R). While the C-terminal domain of AGRP, AGRP(87-132), is equipotent to the full-length peptide, further truncation decreases potency at the MC3R and MC4R. Herein, we report AGRP-derived peptides designed to mimic the active β-hairpin secondary structure that contains the hypothesized Arg-Phe-Phe pharmacophore. The most potent scaffold, c[Pro-Arg-Phe-Phe-Asn-Ala-Phe-DPro], comprised th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
135
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(148 citation statements)
references
References 77 publications
13
135
0
Order By: Relevance
“…54 The most potent substitution, Asn to diaminopropionic acid (Dap), resulted in a ligand that was equipotent to the C-terminal domain of AGRP at the MC4R. 54 It was previously hypothesized that the active loop Asn residue in AGRP may be in close proximity to an Asp residue in the MC4R (Asp 189 ), and that incorporation of basic residues into AGRP analogues at this position might form a novel salt bridge with the MC4R. 47 While the increased potency observed for basic substitutions supported the postulated salt bridge, the increased potency for Gly suggested other residues might also be incorporated without diminishing potency.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…54 The most potent substitution, Asn to diaminopropionic acid (Dap), resulted in a ligand that was equipotent to the C-terminal domain of AGRP at the MC4R. 54 It was previously hypothesized that the active loop Asn residue in AGRP may be in close proximity to an Asp residue in the MC4R (Asp 189 ), and that incorporation of basic residues into AGRP analogues at this position might form a novel salt bridge with the MC4R. 47 While the increased potency observed for basic substitutions supported the postulated salt bridge, the increased potency for Gly suggested other residues might also be incorporated without diminishing potency.…”
Section: Resultsmentioning
confidence: 99%
“…54 A macrocyclic scaffold containing the active hexapeptide loop of ARGP cyclized through a DPro-Pro motif, c[Pro-Arg-Phe-Phe-Asn-Ala-Phe-DPro], was 50-fold less potent at the MC4R compared to AGRP. 54 Further structure-activity relationship studies at the Asn position indicated basic residues (diaminopropionic acid [Dap], diaminobutyric acid [Dab], Orn, Lys, Arg) or Gly increased MC4R potency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scaffolds reported by Ericson et al . were AGRP macrocyclic derivatives [133]. The antagonist reported by Lensing et al .…”
Section: Selective Compoundsmentioning
confidence: 99%